RESTORATIVE RESOLUTION OF CHILD CASES IN THE IMPLEMENTATION OF THE CHILD CRIMINAL JUSTICE SYSTEM - Deriana, Nadya; Puspasari, Ratih Mega (UNISSULA Semarang, 2024)
This study aims to examine the application of the RESTORATIVE concept in resolving child cases in the juvenile criminal justice system in Indonesia. The restorative approach in juvenile criminal justice emphasizes the recovery of victims, perpetrators, and society, compared to an approach that only focuses on punishment. This study examines how legal mechanisms that prioritize children's interests can be applied effectively in an effort to minimize the negative impact of the criminal justice system on juvenile perpetrators. The method used in this study is the normative legal method with a statutory approach and analysis of related documents. Data were obtained through a literature study of laws and regulations, scientific journals, and documents relevant to juvenile criminal justice and the restorative approach. The data collected were then analyzed qualitatively to understand the application of the RESTORATIVE concept in various cases of juvenile cases. The results of the study indicate that the restorative approach in resolving juvenile cases significantly reduces the rate of repeat criminal acts by children and improves psychological well-being for both child perpetrators, victims, and the community. This system encourages social responsibility and a more humanistic reconciliation process, but still faces obstacles in its application in the field due to limited understanding and coordination between stakeholders.